Application of Pancasila Values In Growing a Sense of Nationalism For Young Generations In The Era of Globalization - Somantri, Diki; Anggraeni Dewi, Dinie (CV. Media Publikasi Profesional, 2021)
This study aims to provide an overview of the application of Pancasila values in fostering a sense of nationalism for the younger generation in this era of globalization. The research method is to use a qualitative approach with literature studies, looking for all information in various journals and document sources. The results showed that the young generation has now been carried away by globalization. The younger generations have adopted many western styles of life. For example, the younger generation prefers to use foreign products compared to local products or domestic products. This shows that a sense of nationalism or a sense of nationality needs to be cultivated in an era of globalization like this, by applying the values of Pancasila in everyday life.